On the role of international benchmarking of electricity transmission system operators facing significant investment requirements - Gert Brunekreeft (Jacobs University Bremen, Bremer Energie Institut, 2012)
Electricity networks currently face massive investment requirements. This paper argues that, given the investment requirements, (international) benchmarking is not an adequate tool for the regulation of transmission system operators (TSO). Errors in the outcomes of benchmarking will likely distort network investment and therefore the costs of doing it wrong are high. The paper discusses options to reduce the weight of benchmarking in TSO regulation and options that do not rely on benchmarking at all. Overall, facing massive investment requirements, it seems desirable to switch to a regulatory system with ex-ante investment approval and away from ex-post benchmarking.
Keywords: D42; G00; L51; 330; electricity; network; regulation; benchmarking; uncertainty